2022
DOI: 10.1136/bmjophth-2021-000966
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of the readability and quality of online patient education materials for the medical treatment of open-angle glaucoma

Abstract: ObjectivePatient adherence to glaucoma medications is poor, and is linked to low literacy levels. Patients commonly use the internet to access health information, and it is recommended that patient information is written at an 11-year-old reading level. The aim of this study is to assess the readability and quality of online patient education materials for the medical management of open angle glaucoma.Methods and analysisThe top 10 relevant Google searches for nine glaucoma medications (timolol, brimonidine, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
15
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 35 publications
1
15
0
1
Order By: Relevance
“…Many internet users seek health-related information, but most internet information comes from unregulated or unverified sources and may be unreliable. 1,2 Artificial intelligence (AI) language platforms can respond interactively to user inquiries by generating paragraph-form responses. 3 Given these platforms' popularity, large language model (LLM)-based platforms, such as chatbots, may be used for health information.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Many internet users seek health-related information, but most internet information comes from unregulated or unverified sources and may be unreliable. 1,2 Artificial intelligence (AI) language platforms can respond interactively to user inquiries by generating paragraph-form responses. 3 Given these platforms' popularity, large language model (LLM)-based platforms, such as chatbots, may be used for health information.…”
mentioning
confidence: 99%
“…Patients require accurate information about ophthalmic conditions to make informed medical decisions. Many internet users seek health-related information, but most internet information comes from unregulated or unverified sources and may be unreliable . Artificial intelligence (AI) language platforms can respond interactively to user inquiries by generating paragraph-form responses .…”
mentioning
confidence: 99%
“…They found online material to be of low quality with poor readability scores, requiring an 11th grade level or higher 16 . Other studies have produced similar findings on the topic of glaucoma 17–19 …”
Section: Introductionmentioning
confidence: 78%
“…16 Other studies have produced similar findings on the topic of glaucoma. [17][18][19] Glaucoma is the leading cause of irreversible blindness worldwide, and it affects the lives of over 60 million people. 20,21 Despite the availability of various pharmacologic and laser therapies, many patients require glaucoma surgery to better control their disease.…”
Section: Introductionmentioning
confidence: 99%
“…The findings indicated that 229 studies evaluated readability in the context of patient education, with 91 of those evaluated using only readability criteria (Abdul Rahman et al, 2020;Ahmadzadeh et al, 2014;Al Aqeel et al, 2018;Alderson et al, 2020;Alejos et al, 2021;Alpaydin et al, 2021;Alshaikh et al, 2021;Alshehri & Joury, 2019;Alwani et al, 2021;Ang et al, 2022;Arif & Ghezzi, 2018;Arslan et al, 2020;Avancini et al, 2021;Azer et al, 2017;Azer et al, 2018;Bacher et al, 2020;Bai et al, 2019;Barnes & Davies, 2015;Bernstam et al, 2005;Best et al, 2015;Betschart et al, 2017;Bojrab 2nd et al, 2020;Boureanu et al, 2021;Brennan et al, 2021;Carden et al, 2007;Cheah et al, 2020;Cheng et al, 2016;Choudhery et al, 2020;Colaco et al, 2013;Coleman et al, 2022;Cook et al, 2017;Corredera et al, 2018;Crabtree & Lee, 2022;Dalton et al, 2015;Davis et al, 1998;De Felippe & Kar, 2015;Docimo Jr. et al, 2022;Dorcely et al, 2015;Doubleday et al, 2021;…”
Section: Acknowledgementsmentioning
confidence: 99%